Astronomy Center Di Bukittinggi Dengan Penerapan Prinsip Desain Daniel Libeskind - Wahyu Prima Putra; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Astronomy Center is an education and research tourism destination that collects all forms of activities and needs for astronomy. The importance of the role of astronomy for Indonesian people who mostly live from farming and sailing, as well as an increase in astronomy centers, driven by the construction of facilities that can accommodate complex activities in the field of astronomy. Bukittinggi was chosen as design location because it fulfilled various special requirements in the construction of the Astronomy Center. Astronomy Center Design applies Daniel Libeskind's design principles based on his design thinking and explores broad ideas. The design method used consists of literature data, interviews, and field surveys for data installation. The main concept of the design was named "The Born of the Star", which was taken from one of the phenomena in astronomy, namely "Supernova Phenomenon (Star Formation)". The stage of the formation of the Supernova phenomenon was also applied as a design transformation.Keywords: Astronomy Center, Bukittinggi, Daniel Libeskind, Supernova..